(3GddHGH aj eYQaI GdCfSGHs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfqj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ , J (B630 (3g`s; (3YHO GdcQje Hf eMeO Hf efUhQ GdJejej GdSeYGfj GdeQhRj, CHh SYO,J (B562 (3g` s
(3ChdgG (B:s
(3hjHOC ef MQa GdOGd s
(3BNQgG (B:s
(3hjfJgi HBNQ MQa GdZjf s
(3HChdg Jedc deMeO Hf CMeO NWjH OGQjGs
(3hHBNQg NW GdeDQN TeS GdOjf Hf NdcGf HGdebGHdIs
(3hCjVkG NW GdYdGeI bWH GdOjf GdNjVQi HGdeWGdYIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs